Prevalence of caregiver hesitancy for vaccinations in children and its associated factors: A systematic review and meta-analysis. - Nur Hasnah Maamor; Nor Asiah Muhamad; Nor Soleha Mohd Dali; Fatin Norhasny Leman; Izzah Athirah Rosli; Tengku Puteri Nadiah Tengku Bahrudin Shah; Nurul Hidayah Jamalluddin; Nurul Syazwani Misnan; Zuraifah Asrah Mohamad; Sophia Karen Bakon; Mohd Hatta Abdul Mutalip; Muhammad Radzi Abu Hassan; et al. (PLoS ONE)
This review aimed to systematically compare and pool the prevalence of all the known evidence on caregiver hesitancy and to describe the factors influencing vaccine hesitancy among caregiver worldwide such as COVID-19, MMR, Influenza, HPV and others. We searched article from few electronic databases (PubMed, CENTRAL, ProQuest, and Web of Science) from inception to August 2023 using specific keywords for example caregiver, parents, prevalence, factor, hesitancy, and others. We included population-based studies that reported the prevalence of caregiver hesitancy. We used random-effects meta-analyses for pool prevalence estimates of caregiver hesitancy. A total of 765 studies met our inclusion criteria, containing data on 38,210,589 caregivers from seven regions across the globe. Overall or pool prevalence of vaccine hesitancy among caregiver is 25.0% (95% CI: 0.22-0.27, I2 = 99.91%, p = 0.001). Based on the evidence gathered, vaccine hesitancy was found to be religious sentiments, personal beliefs, perceived safety concerns, and a desire for more information from healthcare providers, along with factors related to availability, accessibility, affordability, and acceptability of vaccinations. Vaccine safety and efficiency have been identified as the main factor for caregiver vaccine hesitancy globally with a prevalence of 91.4%. Trial registration PROSPERO registration number: CRD42022331629. https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022331629.